2012
DOI: 10.1108/13552551211204229
|View full text |Cite
|
Sign up to set email alerts
|

Strategic innovation and new product development in family firms

Abstract: Purpose -This study aims to investigate the relationship between the presence of the family variable within a business enterprise and the managerial factors affecting the success of new product development (NPD). This can be structured into three research questions: What is the relationship between the presence of the family variable within a business enterprise and the managerial factors affecting the success of NPD activities? How the managerial factors affecting the NPD process are faced in family firms? Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 129 publications
3
143
0
11
Order By: Relevance
“…Family members from different generations may resist openly sharing knowledge with one another if strong conflicts mark their relationships (Cassia et al, 2012;Sonfield & Lussier, 2004). Conflict in family firms arises in different forms, such as disagreements about content-related or decision-making issues or personal, emotion-based disputes (Hoelscher, 2014;Kellermanns & Eddleston, 2004).…”
Section: Family Conflict Managementmentioning
confidence: 99%
“…Family members from different generations may resist openly sharing knowledge with one another if strong conflicts mark their relationships (Cassia et al, 2012;Sonfield & Lussier, 2004). Conflict in family firms arises in different forms, such as disagreements about content-related or decision-making issues or personal, emotion-based disputes (Hoelscher, 2014;Kellermanns & Eddleston, 2004).…”
Section: Family Conflict Managementmentioning
confidence: 99%
“…Family‐owned SMEs are typically guided by unique norms, cultures, and processes that rarely exist in non‐family counterparts (Kellermanns et al ) and determine family SMEs' decision‐making processes, including innovation. In addition to factors such as nepotism, rigidity, and conflict potential, which are all said to limit these firms' tendency to innovate (Roessl, Fink, and Kraus ), risk aversion tends to play a crucial role (e.g., Cassia, De Massis, and Pizzurno ). These characteristics generally originate from: (1) blurred boundaries between family and firm equity, since owning families typically invest most of their wealth in their firms (Carney ) to avoid external sources of financial capital (Chrisman and Patel ); (2) an overly strong emphasis on personal interests of the different involved family members; or (3) the desire to carry the firm on to the next generation (Koiranen ).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Based on the described existing evidence, we will explain below the main research lines on the topic that has been identified and proposed. (Cassia et al, 2012;Donckels & Fröhlich, 1991); survival or long-term corporate orientation (Bergfeld & Weber, 2011;Cassia et al, 2011;Cassia et al, 2012;Westhead, 1997); reputation (Westhead, 1997); transgenerational value (Cassia et al, 2011;Chirico & Nordqvist, 2010;; paternalism (Chirico & Nordqvist, 2010); corporate social responsibility (Wagner, 2010); willingness to change Weismeier-Sammer, 2011) -Service-dominant focus (Dibrell & Moeller, 2011) -Stewardship culture (Dibrell & Moeller, 2011) Resource allocation -Debt in RandD financing (Czarnitzki & Kraft, 2009) -External financing Long-term financial orientation (Westhead, 1997) -Financial slack (Grundström et al, 2012;Kim et al, 2008 (Niehm et al, 2010) -Management control systems (Duréndez et al, 2011;Kraus et al, 2012) -Management structures (Kraus et al, 2012) -Size effect (Craig & Dibrell, 2006;Czarnitzki & Kraft, 2004;Duréndez et al, 2011;Galve-Górriz & Salas-Fumás, 2011) -Types of customers (Gudmundson et al, 2003) (Duréndez et al, 2011) -Innovativeness (Casillas & Moreno, 2010;Cassia et al, 2012;Duréndez et al, 2011;Naldi et al, 2007;Short et al, 2009;Zellweger &am...…”
Section: R E S U L T S : a N A L Y S I S O F Determinants And Dimensimentioning
confidence: 99%